2020
DOI: 10.3892/etm.2020.9145
|View full text |Cite
|
Sign up to set email alerts
|

Combined effect of recombinant human adenovirus p53 and curcumin in the treatment of liver cancer

Abstract: The development of an effective therapeutic intervention for liver cancer is a worldwide challenge that remains to be adequately addressed. Of note, TP53, which encodes the p53 protein, is an important tumor suppressor gene, 61% of TP53 is functionally inactivated in liver cancer. Recombinant human adenovirus p53 (rAd-p53) is the first commercial product that has been used for gene therapy. In the present study, the combined mechanistic effects of rAd-p53 and curcumin, a naturally occurring compound with previ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…PI3K is a known major regulator for cell survival and apoptosis [ 36 ]. Therefore, downregulation of the PI3K/AKT/mTOR pathway is generally suggested as a therapeutic target for cancer diseases [ 37 , 38 ]. Although few studies have been conducted on PI3K/AKT in endometriosis [ 39 ], in one of the previous studies, phosphorylated AKT was observed in postmenopausal women with ovarian endometriosis [ 40 ], and phosphorylated mTOR was increased in ectopic lesions [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…PI3K is a known major regulator for cell survival and apoptosis [ 36 ]. Therefore, downregulation of the PI3K/AKT/mTOR pathway is generally suggested as a therapeutic target for cancer diseases [ 37 , 38 ]. Although few studies have been conducted on PI3K/AKT in endometriosis [ 39 ], in one of the previous studies, phosphorylated AKT was observed in postmenopausal women with ovarian endometriosis [ 40 ], and phosphorylated mTOR was increased in ectopic lesions [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our results indicated that fraxetin affects the cell cycle and proliferation via the MAPK signaling pathway. Similarly, a previous study indicated that curcumin suppresses metastasis and induces the G2/M phase arrest by upregulating the JNK expression in liver cancer [ 36 ]. Although fraxetin did not affect the phosphorylation of ERK1/2, it dramatically reduced the expression of P90RSK, which is downstream of ERK1/2.…”
Section: Discussionmentioning
confidence: 78%
“…And these proteins control a diversity of cellular responses, such as cell growth, cell proliferation, cell differentiation, cell survival and cell death. The aberrant expression and activation of JNKs are found in many cancer cell lines and tissue samples ( Mohebali et al, 2020 ; Qu et al, 2020 ). In primary hepatocellular carcinoma (HCC), compared with the non-neoplastic lesions, the activation of JNK1 in tumor size was significantly increased, and absence of JNK1 impaired hepatocyte proliferation and tumor formation ( Chang et al, 2009 ; Gao et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%